ANALISIS HUBUNGAN LABA BERSIH, ARUS KAS OPERASI DAN RUPS DENGAN DIVIDEN TUNAI PADA INDUSTRI MANUFAKTUR - Masrifah, Ifah (LPPM Universitas Terbuka, 2014)
The study is an empirical study to examine the effect of positive Net Income (EAT), Operating Cash Flow (CFO) and RUPS with a cash dividend on the manufacturing industry (An application of panel data). Techniques for taking a purposive sample with the total sample of 18 companies consecutive pay cash dividends for period 2007-2011. The design of this study is included quantitative research. Research tools used in the testing is the analysis method of panel. The result is a positive significant relationship between net income with cash dividends that pointed by the amount of beta standardized coefficients value 0,352 with a probability value of 0,000. Operating cash flow and RUPS results are positive but unsignificant with cash dividends that pointed by the amount of beta standardized coefficients value are 0,138 with a probability value of 0,210, and RUPS are 0,016 with a probability value of 0,913. Significant relationship means that the value of cash dividends is influenced significantly by the value of net income. Whereas unsignificant relationship means that the value of cash dividends isn't influenced significantly by the value of of the operating cash flow and RUPS.   Penelitian ini merupakan studi empiris untuk menguji pengaruh positif Laba Bersih (EAT), Arus Kas Operasi (CFO) dan RUPS dengan dividen tunai pada perusahaan manufaktur (Suatu penerapan data panel). Pengambilan sampel yang digunkana adalah purposive dengan jumlah sampel sebanyak 18 perusahaan yang berturut-turut membayar dividen tunai selama tahun 2007-2011. Desain penelitian ini adalah termasuk penelitian kuantitatif. Alat yang dipakai dalam pengujian adalah analisis metode panel. Hasilnya adalah hubungan positif yang signifikan antara laba bersih dengan dividen kas yang ditunjukkan dari nilai koefisien beta standardized-nya yaitu 0,499 dengan nilai probabilitas sebesar 0,000. Arus kas operasi nilai koefisien 0,300 dan nilai probabilitas sebesar 0,210, RUPS dengan nilai koefisien 0,254 dan nilai probabilitas sebesar 0,913, hasilnya positif namun tidak signifikan dengan dividen kas. Hubungan yang signifikan berarti bahwa nilai dividen kas dipengaruhi secara signifikan oleh nilai laba bersih. Sedangkan hubungan tidak signifikan berarti bahwa nilai dividen kas tidak dipengaruhi secara signifikan oleh nilai dari arus kas operasi dan RUPS.